Membrane permeability and antimicrobial peptides : much more than just making a hole : much more than just making a hole - Maffia, Paulo César (American Peptide Society, 2023)
Antimicrobial peptides (AMPs) are one of the elements of innate immunity that have a crucial role in fighting infections. These molecules are produced by all kinds of cells and can display a wide spectrum of action against bacterial or fungal infections. Bacterial resistance toward broad-spectrum antibiotics has become a major concern in recent years. In this context, AMPs have emerged as promising alternative therapy in response to this increasing problem because of their ability to inhibit growth and biofilm formation, even in drug-resistant microorganisms. However, despite the myriad of patents filed related to AMPs, only a small proportion of AMPs have already received certification, either by the Food and Drug Administration (FDA) or European Medicines Agency (EMA). In order to pave the way of AMPs to certification, a comprehensive knowledge of the mechanism of action of these peptides is essential. Several models have been proposed to explain it and the permeabilization of the bacterial envelope seems to play a key role in most of them. In this review, we describe the different techniques that are generally used to assess the permeabilization induced by AMPs in either in vivo or in vitro systems. Additionally, a comprehensive analysis of the cooperation during the process of binding and permeabilization is included.
Keywords: Ciencias naturales::Ciencias biológicas::Biología celular, Microbiología